Interobserver reproducibility of maximal axial diameter and tumour volume measurements from CT of patients with head and neck squamous cell carcinoma. Issue 11 (November 2017) - Chung, M.S.; Choi, Y.J.; Lee, S.S.; Lee, J.H.; Lee, Y.S.; Rho, J.L.; Baek, J.H.
Abstract : Aim: To evaluate the interobserver reproducibility of computed tomography (CT) measurements of maximum tumour diameter and tumour volume for head and neck squamous cell carcinoma. Materials and methods: Eighty consecutive patients who underwent neck CT for the initial evaluation of head and neck squamous cell carcinoma were included in this retrospective study. Two radiologists independently measured the maximal axial diameter and volume of tumours. The reproducibility between the two observers was assessed using 95% Bland–Altman limits of agreement, reproducibility coefficient, within-subject coefficient of variation, and intraclass correlation coefficient with subgroup analysis according to tumour location. Logistic regression analysis was performed to identify the risk factors for high variability in tumour volume. Results: The 95% limits of agreement for maximal axial diameter and tumour volume were ±22.3% and ±42.8%, respectively. The within-subject coefficient of variation and reproducibility coefficient were 7.9% and 0.564 for maximal axial diameter and 22.9% and 5.069 for tumour volume. All intraclass correlation coefficients for maximal axial diameter and tumour volume demonstrated excellent agreement (all intraclass correlation coefficients >0.9). Peritumoural infiltration (odds ratio: 7.189; confidence interval: 1.815–28.469; p =0.005) was an independent risk factor for high interobserver variability. Conclusion: Changes in maximum axial diameter and tumour volume of <22.3% and 42.8%, respectively, were in the range of measurement error on CT. The presence of peritumoural infiltration on CT increases the error in tumour volume measurement. Highlights: Changes in diameter and volume ≤ 22.3% and 42.8% in HNSCC were in the range of measurement error on CT. The peritumoural infiltration on CT increases the error in tumour volume measurement. Tumour volume change in HNSCC should be carefully interpreted for measurement error using CT.